2021
DOI: 10.25259/sni_371_2021
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculostomy supply cart decreases time-to-external ventricular drain placement in the emergency department

Abstract: Background: Minimizing time-to-external ventricular drain (EVD) placement in the emergency department (ED) is critical. We sought to understand factors affecting time-to-EVD placement through a quality improvement initiative. Methods: The use of process mapping, root cause analyses, and interviews with staff revealed decentralized supply storage as a major contributor to delays in EVD placement. We developed an EVD “crash cart” as a potential solution to this problem. Time-to-EVD placement was tracked pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This highlighted that access to equipment was a cause of time delay and subsequently, creating a ventriculostomy trolley, significantly reduced time to ventriculostomy. 25 In spine surgery, Lui et al paired lean principles with process mapping to identifying time saving areas for patients undergoing lumbar spinal fusion surgery. The study identified that instrument defects were a cause of 66% of the time delay intraoperatively, a crucial finding in streamlining the efficiency of lumbar fusion procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This highlighted that access to equipment was a cause of time delay and subsequently, creating a ventriculostomy trolley, significantly reduced time to ventriculostomy. 25 In spine surgery, Lui et al paired lean principles with process mapping to identifying time saving areas for patients undergoing lumbar spinal fusion surgery. The study identified that instrument defects were a cause of 66% of the time delay intraoperatively, a crucial finding in streamlining the efficiency of lumbar fusion procedures.…”
Section: Discussionmentioning
confidence: 99%
“…“Ventriculostomy supply cart decreases time‐to‐external ventricular drain placement in the emergency department,” United States 6 …”
Section: Author Year Of Publication Article Title Country Of Origin A...mentioning
confidence: 99%
“…Both studies identified increases in resource availability and the potential for increased efficiency in accessing required supplies with the implementation of cart systems. Additionally, Chang et al 6 examined implementation of a ventriculostomy supply cart. They found that improved access to preassembled equipment led to significant decreases in time to intervention.…”
Section: Author Year Of Publication Article Title Country Of Origin A...mentioning
confidence: 99%
See 1 more Smart Citation
“…This team noted they would have to visit approximately two to four supply closets to gather the appropriate materials for commonly performed procedures such as central and arterial lines. Decentralized supply storage has been shown to significantly delay emergency procedures such as ventriculostomy for example [1]. After several months of struggling with this inefficient system, this team proposed the idea of a procedure cart to the Emergency Department staff and administration.…”
Section: Introductionmentioning
confidence: 99%